PENGARUH PREDIKSI KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI TERHADAP HARGA SAHAM - Fara Fitriyani (Universitas Merdeka Madiun, 2022)
This study aims to examine the effect of the Altman Z-Score, Springate and Zmijewski method on stock prices. This research is a type of quantitative research. The population of this study are pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2020. The number of companies that became the research sample was 31 companies. Data were analyzed using a simple regression analysis model using IBM SPSS 23 software. The results of this test are 1) Altman z-score has a negative effect on stock prices, so it can be concluded that hypothesis 1 is accepted 2) . These results indicate that the springate variable has a positive effect on stock prices, so it can be concluded that hypothesis 2 is accepted. 3) the zmijewski x-score variable has a negative value with a significant value below 5% of the stock price, so it can be concluded that hypothesis 3 is accepted